Caso de estudio: análisis y diagnóstico de una empresa del sector agroindustrial peruano, propuesta de un plan estratégico - Espinoza Reyes, Renato Edén (2019)
In this paper, the Peruvian non-traditional agro-export company Camposol has been analyzed, which was ranked number 1 in the ranking of the sector in 2016 and is one of the main employers in the country. For this analysis, various concepts, procedures and techniques learned throughout the Administration career at the “Universidad de Lima” have been used as a methodology, such as: PEST Analysis, Porter forces analysis, SWOT matrix, EFI Matrix , EFE Matrix, Balance Scorecard, among others. In addition, al lof them have been included in the following structure: internal and external analysis, identification and proposal of strategies, implementation of the proposed strategies and, finally, control and measurement of the results obtained.